2016
DOI: 10.1016/j.janxdis.2016.04.001
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with practitioners’ use of exposure therapy for childhood anxiety disorders

Abstract: The current study examines factors related to use of exposure therapy by clinicians who treat children with anxiety disorders. A sample of 331 therapists from a variety of backgrounds (i.e., social workers, doctoral psychologists, masters level counselors, and marriage and family therapists) completed a survey regarding use of exposure and other treatment techniques for childhood anxiety disorders, as well as beliefs about exposure and child resiliency. Although the majority of therapists endorsed a CBT orient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
118
2
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 142 publications
(138 citation statements)
references
References 37 publications
15
118
2
3
Order By: Relevance
“…Emerging neuroscience research also supports the importance of contextually based fear extinction learning, particularly for adolescents (Pattwell et al, 2016). However, many therapists report not using exposure-focused CBT due to beliefs that exposure may exacerbate patient anxiety, cause undue harm, or be otherwise unsafe or intolerable (Whiteside et al, 2016). Our findings indicate that exposure-based CBT at best improves secondary outcomes and, at a minimum, does not likely lead to worsening of the psychiatric symptoms we measured.…”
Section: Discussionmentioning
confidence: 99%
“…Emerging neuroscience research also supports the importance of contextually based fear extinction learning, particularly for adolescents (Pattwell et al, 2016). However, many therapists report not using exposure-focused CBT due to beliefs that exposure may exacerbate patient anxiety, cause undue harm, or be otherwise unsafe or intolerable (Whiteside et al, 2016). Our findings indicate that exposure-based CBT at best improves secondary outcomes and, at a minimum, does not likely lead to worsening of the psychiatric symptoms we measured.…”
Section: Discussionmentioning
confidence: 99%
“…This same sample was also used to examine treatment practices in a study reported elsewhere (Whiteside, Deacon, Benito, & Stewart, 2016). Two hundred and sixty-five of the respondents provided their profession, which included social workers (SW; n = 113, 42.6%), doctoral level psychologists (PhD; n = 49, 18.5%; and PsyD; n = 31, 11.7%), masters degree licensed counselors ( n = 44, 16.6%), and marriage and family therapists (MFT; n = 28, 10.6%).…”
Section: Methodsmentioning
confidence: 99%
“…These are also the disorders covered by commonly used structured diagnostic interviews and rating scales (i.e., Silverman & Albano, 1996 and Birmaher et al, 1997 respectively). These clinicians were emailed a follow-up survey about their assessment (current study) and treatment practices (Whiteside, Deacon, Benito, & Stewart, 2016). A total of 339 respondents completed the questions regarding EBA and were included in the current study.…”
Section: Methodsmentioning
confidence: 99%
“…Use of exposure, or confronting fear stimuli within the context of CBT, is the key ingredient of intervention leading to improved outcomes (Kendall et al, 2006; Peris et al, 2015). Despite scientific recognition that exposure is critical to the success of CBT for anxiety, recent estimates suggest that only 10–30 percent of clinicians endorse using exposure therapy in routine clinical care (Becker, Zayfert, & Anderson, 2004; Borntrager, Chorpita, Higa-McMillan, Daleiden, & Starace, 2013; Trask, Fawley-King, Garland, & Aarons, 2016; Whiteside, Deacon, Benito, & Stewart, 2016; Wolitzky-Taylor, Zimmermann, Arch, De Guzman, & Lagomasino, 2015). To date, most studies examining exposure use in the context of routine clinical care have largely focused on documenting the rates of exposure use with adult clients with anxiety or post-traumatic stress disorder (PTSD); the few studies with youth populations suggest comparably low rates of exposure use for anxious youth (Higa-McMillan, Kotte, Jackson, & Daleiden, 2016; Whiteside et al, 2016).…”
Section: Introductionmentioning
confidence: 99%